Knowledge Construction as Socially Embedded Collective Learning - Bo Chang (Adult Education Research Conference, 2010)
This paper discusses how knowledge construction is a socially embedded collective learning through analyzing learning embodied in five specific patterns of knowledge construction. The analysis reveals that knowledge construction is socially imbedded in the empirical world and is generally a collective activity.